Prolonged release of antiepileptic drugs: Pharmaceutical strategies and impacts on patient’s quality of life (Research, Society and Development, 2025)
Epilepsy is a chronic neurological disorder characterized by abnormal electrical discharges in the brain, which trigger seizures of varying intensity and duration. In addition to neurological manifestations, the condition can affect the patient’s emotional well-being and place a burden on family members and caregivers. Treatment is carried out through the use of antiepileptic drugs, which can be immediate-release or extended-release. Immediate-release medications require multiple daily doses and present greater variation in blood concentration, which may increase adverse effects. Extended-release drugs gradually release the active ingredient, maintaining stable plasma levels, reducing dosing frequency, and promoting treatment adherence. In this context, an integrative literature review was conducted to compare the efficacy, safety, and adherence between immediate-release and extended-release medications. It is concluded that extended-release antiepileptics show better outcomes regarding seizure control, treatment adherence, and patient quality of life, representing a promising strategy in the pharmacological management of epilepsy.